Pengembangan Kurikulum Magister Ekonomi Syariah Perguruan Tinggi Keagamaan Islam Negeri (Ptkin) Di Era Revolusi Industri 4.0 - Wibowo, Muhammad Ghafur (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
The Master Program in sharia economics (MES) is one of the study programs that are widely available at State Islamic Religious Universities (PTKIN), consist of State Islamic Universities (UIN), State Islamic Institutes (IAIN), and State Islamic Colleges (STAIN). More than 30 of all PTKIN in Indonesia have MES study programs, but preliminary observations show that the curriculum content of the 30 MES programs is still varied and not standardized. This study aims to analyze the variability of the curriculum content of Islamic Economics Master Program at PTKIN in Indonesia and formulate a minimum curriculum content standard that should be applied in all Islamic Economics Master Program at PTKIN in Indonesia. The results showed that there are 13 recommended courses, namely microeconomics, macroeconomics, philosophy of Islamic economics, history of economic thought Islam, economic verses and hadith, usul Fiqh, Fiqh muamalah, Islamic economic systems and theories, research methods, econometrics, economic mathematics, Sharia digital financial economics, and thesis. The choice of courses is based on accommodation to economic theory, Sharia Science, Industrial Revolution 4.0, SNPT fulfillment, KKNI fulfillment, and Outcome Education Education (OBE) base. In addition, the compulsory courses are also in line with the courses taught in the master's program in economics (MIE) at the PTUN, which in fact are more established and more experienced. Finally, the compulsory subjects are also generally in line with the academic terms of reference of the S1 Islamic Economics Study program issued by KNEKS.